THE MODERATING ROLE OF TYPE OF UNIVERSITY IN THE RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP AND SUPPLY CHAIN MANAGEMENT: EVIDENCE FROM UNIVERSITIES IN THE KURDISTAN REGION OF IRAQ - Waisy, Omar Hussein; Wei, Chong Chin (International Journal of Supply Chain Management, 2019)
Abstract- This paper aims to explore the extent to which the type of university affects the link between transformational leadership and supply chain management (SCM), in the Kurdistan Region of Iraq. This paper uses quantitative methods to study the link between the main variables. The data were gathered from 611 lecturers in 14 public and 11 private universities in the Kurdistan Region. SmartPLS3 was used to evaluate measurement model and structural model. The results show a significant correlation between transformational leadership and readiness for change. Smart PLS results show that type of university were found to not have an effect on the correlation between these two variables. This paper contributes to existing literature by presenting a more complete understanding for practitioners and researchers of the potential effect of transformational leadership during organisational change by investigating its effect on the readiness for change by the moderating role of type of university.